HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DAN KECEPATAN LARI 40 YARD DENGAN HASIL LOMPAT JAUH GAYA JONGKOK MAHASISWA PUTRA II A PENJASKESREK ANGKATAN 2013 UNIVERSITAS RIAU - Sri Wahyuni Wahyuni; Slamet '; Saripin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem in this study originated from the observation that the authors find that researchers in the field to meet the deficiencies in the run prefix as yet maximal running speed and leg power when the student will be refused on the foundation board is still not optimal, resulting in sub-optimal outcomes leap. The purpose of this research was to determine the relationship of explosive leg muscle power and speed to run 40 yards with the results of the long jump squat style student son Penjaskesrek Force II A 2013 University of Riau. The population in this study were student athletes son II A 2013 University of Riau Penjaskesrek force numbering a total of 39 people using a sampling technique in which all the population sampled, it is not necessary t test. To obtain research data used Without Prefix Long Jump test for explosive leg muscle power, speed test ran 40 yards for a 40-yard run speed, and style Long Jump The long jump squat for squat style. Data were analyzed with a simple product moment correlation. Based on the correlation analysis of the data obtained by rhitung X1 with Y = 0.99> rtable = 0.320 and X2 with Y for rhitung = 0.91> rtable = 0.320 while X1 and X2 with Y for rhitung = 0.99> rtable = 0,320. Because the entire relationship shown in the data analysis significantly, thus Ho is rejected and Ha accepted. This means that there is a relationship of explosive leg muscle power and speed to run 40 yards with the results of the long jump squat style student son Penjaskesrek Force II A 2013 University of Riau. Where the prablovisions of a variable correlation with other variables determined from rhitung> rtable. Keywords: Limb Muscle Explosive Power, Speed ​​40 Yard Run, Squat Style Long Jump Results